Identification of cytotoxic, glutathione-reactive moieties inducing accumulation of reactive oxygen species via glutathione depletion. Issue 8 (1st May 2018) - Wilke, Julian; Kawamura, Tatsuro; Watanabe, Nobumoto; Osada, Hiroyuki; Ziegler, Slava; Waldmann, Herbert
Graphical abstract: Abstract: Reactive oxygen species (ROS) play an essential role in the survival and progression of cancer. Moderate oxidative stress drives proliferation, whereas high levels of ROS induce cytotoxicity. Compared to cancer cells, healthy cells often exhibit lower levels of oxidative stress. Elevation of cellular ROS levels by small molecules could therefore induce cancer-specific cytotoxicity. We have employed high-throughput phenotypic screening to identify inducers of ROS accumulation. We found 4, 5-dihalo-2-methylpyridazin-3-one (DHMP) and 2, 3, 4, 5(6)-tetrachloro-6(5)-methylpyridine (TCMP) moieties to strongly deplete GSH, to cause ROS accumulation and to induce cell death. Small molecules containing these fragments will most likely share the same properties and should therefore be carefully considered in the development of bioactive molecules.